Towards sustainable agriculture in SAARC countries: exploring the long-run impact of GHG emissions on agricultural productivity - Chandio, A. A.; Gokmenoglu, K. K.; Ahmad, F.; Li, J. (Springer, 2023)
The primary aim of this research is to investigate the long-run impact of carbon dioxide (CO2), methane (CH4), nitrous oxide (N2O), and arable land (ARL) on agricultural productivity (AGP) in SAARC countries from 1965 to 2016. To discover the long-term associations and causation among the underlying variables, robust panel co-integration methods, panel FMOLS and DOLS long-run estimators, and panel causality tests are employed. Panel co-integration results show a long-term link between agricultural production, CH4, N2O, CO2, and arable land. The key findings from FMOLS and DOLS indicate that methane and nitrous oxide have a negative impact on agricultural output, while carbon dioxide and arable land have a beneficial impact in the long-run analysis. The causality tests outcomes reveal that long-run causation is substantial for all variables tested. Furthermore, there is bidirectional causality between agricultural output and methane. The link between nitrous oxide and agricultural output is unidirectional. The causation between agricultural output and CO2 emissions is two-way, but in the short run, the connection running from CO2 emissions to agricultural output is stronger than the converse. As a result, the SAARC countries require stronger national measures to curb GHG emissions and reduce the negative long-run impact of extreme climate shocks on agricultural output.
Keywords: GHG emissions; Agricultural productivity; Panel co-integration; SAARC countries